(untitled) (The International Journal for Scientific Research, 2026)
This study aimed to analyze the impact of artificial intelligence applications on the quality of digital transformation practices in governmental institutions, through an applied study on the Saudi Data and Artificial Intelligence Authority (SDAIA). The study was motivated by a research gap reflected in the limited linkage in previous studies between artificial intelligence applications and the quality of digital transformation practices in governmental institutions. The study adopted the descriptive-analytical and inductive approaches. Data were collected using a questionnaire distributed to a sample of SDAIA employees to analyze artificial intelligence practices and digital transformation practices. The findings revealed a positive impact of artificial intelligence applications on improving the quality of digital transformation practices by enhancing decision-making, increasing operational efficiency, and improving the quality of digital services. The results also emphasized the importance of technical infrastructure availability, the development of human competencies, and the enhancement of organizational frameworks and governance, contributing to the achievement of Saudi Vision 2030 objectives and strengthening governmental performance efficiency.